MECHANISMS OF ARTERIAL AND VENOUS HYPEREMIA - Umurov Erkin Utkirovich (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Arterial and venous hyperemia represent two distinct forms of increased blood flow  to  tissues,  each  with  different  underlying  mechanisms  and  physiological implications. Arterial hyperemia refers to an increase in blood flow due to vasodilation of arterioles, while venous hyperemia is caused by impaired venous return and venous congestion.  Both  forms  of  hyperemia  are  important  in  understanding  various cardiovascular  conditions,  including  inflammation,  ischemia,  and  organ  perfusion. This article explores the mechanisms behind arterial and venous hyperemia and their clinical relevance.